The Influence of Marketplace Algorithm Transparency on Consumer Trust and Online Purchasing Decisions in Indonesia - Erwinda, Maria; Asriyanti, Yohana (Universitas Sains dan Teknologi Komputer, 2025)
The rapid growth of digital marketplaces in Indonesia has raised critical issues regarding consumer trust in algorithmic recommendation systems that operate invisibly. This study aims to examine the influence of marketplace algorithmic transparency on consumer trust and online purchase decisions in Indonesia. A quantitative explanatory approach was applied through a survey of 250 active users from leading marketplaces such as Tokopedia, Shopee, and Lazada.Data were examined using Partial Least Squares–Structural Equation Modeling (PLS-SEM) technique through the support of SmartPLS 4.0 software. Results showed that algorithmic transparency has a significant and positive influence on consumer trust, and consumer trust partially mediates the relationship between algorithmic transparency and online purchase decision. High predictive power of the model is evidenced by the R² score of 0.63 and Q² of 0.41. These findings highlight that not only does digital transparency heighten digital trust, but also strengthens consumer loyalty on online marketplaces. The contribution of this study is that it empirically validates the association among algorithmic transparency, trust, and buying behavior under the distinct digital culture in Indonesia, and provides practical implications for marketplace managers to promote ethically open and responsible AI-based recommendation systems.